2015
DOI: 10.1371/journal.pone.0139584
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of LRP/LR Induces Apoptosis in Breast and Oesophageal Cancer Cells

Abstract: Cancer is a global burden due to high incidence and mortality rates and is ranked the second most diagnosed disease amongst non-communicable diseases in South Africa. A high expression level of the 37kDa/67kDa laminin receptor (LRP/LR) is one characteristic of cancer cells. This receptor is implicated in the pathogenesis of cancer cells by supporting tumor angiogenesis, metastasis and especially for this study, the evasion of apoptosis. In the current study, the role of LRP/LR on cellular viability of breast M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 44 publications
2
24
0
Order By: Relevance
“…22,31 Our study tion, invasion, angiogenesis, ECM remodeling, and apoptosis. 22,32,33 However, laminin-integrin binding has also been reported to modulate neuronal survival through the Akt or focal adhesion kinase signaling pathway. 16,34 Whether the laminin-integrin signaling pathway is involved in ketamine-induced apoptosis needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…22,31 Our study tion, invasion, angiogenesis, ECM remodeling, and apoptosis. 22,32,33 However, laminin-integrin binding has also been reported to modulate neuronal survival through the Akt or focal adhesion kinase signaling pathway. 16,34 Whether the laminin-integrin signaling pathway is involved in ketamine-induced apoptosis needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between RPSA expression and tumour aggressiveness proposes RPSA as a promising strong target in fight against cancer but also in prion diseases and Alzheimer's disease. 18 Therefore, by its multiple functions like maintenance of nuclear structures and translational processes, 58 Only the pharmacological approaches (green tea polyphenol EGCG) can overcome this difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…Besides its normal roles in mediating cell viability, cellular adhesion and functioning as a member of the ribosomal translational machinery, LRP/LR has been implicated in a number of pathological processes including cancer and metastasis [45] . However, the induction of apoptosis in response to downregulation of LRP/LR, as shown here and previously for MCF-7, MDA-MB231and WHCO1 cells [32] , suggests that this may not be a practical approach without specific targeting to avoid inducing apoptosis in non-tumourigenic cells. Interestingly, though, we have previously shown that shRNA mediated downregulation of LRP/LR had no significant effect on the viability of non-cancerous HEK293 cells suggesting that this protein might be crucial for cell survival in certain cell types only [17] .…”
Section: Discussionmentioning
confidence: 61%
“…Due to the involvement of LRP/LR in these aforementioned numerous tumourigenic processes, the role of this receptor in cell survival and viability has become an attractive topic of research [29] . Recent studies showed reductions in the viability of liver (Hep3b) [30] , lung (A549) [31] , cervical (HeLa) [31] , breast (MCF-7 and MDA-MB231) [32] and oesophageal cancer (WHCO1) [32] cells after siRNA-mediated downregulation of LRP/LRthus suggesting that LRP/LR plays a pivotal role in the maintenance of tumour cell viability. Furthermore it has been shown that LRP/LR plays an important role in apoptosis [30][31][32] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation